Understanding the fundamental building blocks of mobile banking adoption: A qualitative approach - Ewe, Soo Yeong *; Yap, Sheau Fen (2012)
The rapid proliferation of mobile phones and other electronic gadgets has not only changed the way people live, but also created a new channel for marketing. One such new technology is the mobile banking development, which can significantly impact a bank’s operational efficiency and customer service aspects. Yet,the adoption of mobile banking in the Asian region has been relatively slow compared to West.One might question, for instance, will mobile banking be as effective as other medium for banking transaction given its limited textual presentation? What do consumers think about mobile banking services? What drives or hinders consumers from adopting mobile banking services? A better understanding of these issues is the key to designing and execution of an effective marketing strategy for mobile banking services. This research aims to explore the underlying motives of mobile banking services adoption. A focus groupdiscussion with eight respondents was conducted to uncover the reasons for using mobile banking. The results suggest that the reasons for using mobile banking is similar to the reasons for engaging in e- commerce as suggested in past literature, for example, perceived advantage over other mediums, perceived risk, usage complexity, and awareness. The finding that the users adopted mobile banking they believe many others haveadopted the same service is novel and should be explored further. The paper concludes with implications to marketing and promoting mobile banking services.